Pengaruh Stres Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Indomarco Prismatama Area Pondok Cabe Tangerang Selatan - Dian Andini; Prasetyo Kurniawan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study was to determine the effect of work stress and work discipline on employee performance at PT Indomarco Prismatama Pondok Cabe Area. This research method uses saturated sampling of 61 respondents. Data analysis uses the SPSS Version 26 program application. The analysis techniques used are validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, correlation coefficient test, determination coefficient test, hypothesis test (t test and f test). The results of this study are work stress has a significant effect on employee performance with a determination coefficient value of 78.5% and the hypothesis test obtained t count> t table (1.346> 2.001). Work discipline has a significant effect on employee performance with a determination coefficient value of 78.5% and the hypothesis test obtained t count> t table (2.133> 2.001). Job stress and work discipline simultaneously significantly impact employee performance, with a regression of Y = 13.127 + 0.186 (X1) + 0.421 (X2). The coefficient of determination is 78.5%, while the remaining 21.5% is influenced by other factors. The hypothesis test yielded a calculated F value > F table, or (110.651 > 3.15).